MODERN APPROACHES TO TEACHING AN AGRONOMY ENGLISH TERMINOLOGY DICTIONARY - Saydamatova Nigora Sheraliyevna (Journals Park Publishing, 2024)
This article explores modern pedagogical approaches to teaching an agronomy English terminology dictionary, emphasizing the importance of effective communication in agricultural education. It discusses the significance of agronomy terminology in understanding and advancing agricultural practices, highlighting its role in facilitating comprehension of academic literature and communication within the agricultural community. The article also examines the evolution of agricultural education and the need for modern teaching methods to adapt to the demands of the digital age.
Keywords: agronomy, English terminology, dictionary, teaching approaches, effective communication, agricultural education, technology, experiential learning, collaborative methods.